Utilização de pastagem de alfafa e raspa de mandioca na produção de leite de cabras - Marques, Raquel Ornelas [UNESP] (2015)
Were used four Saanen goats, non-pregnant and non-lactating, rumen cannulated, kept in feedlot. It was evaluated the replacement of corn and soybean meal by cassava meal and alfalfa, respectively. The experiment was conducted in Latin square design, with diets: MISO: ground corn and soybean meal; MASO: cassava and soybean meal; MIAL: ground corn and alfalfa grazing; MAAL: cassava and alfalfa grazing. Intake, ruminal parameters (pH and ammonia), production of short chain fatty acids (SCFAs) and degradation kinetics of roughage and concentrate were evaluated in adult goats in maintenance. The inclusion of cassava meal and alfalfa didn't affect the intake of dry matter (DM), crude protein (CP), neutral detergent fiber (NDF) and total digestible nutrients (TDN), neither the body weight of goats and the ammonia nitrogen production. The ruminal pH and the production of short chain fatty acids were influenced by the harvest time, and the total SCFA, acetic and butyric acids production showed cubic effect, with maximum production occurring about 4 hours, and minimum 10 hours after the supply of diet. The pH, the production of propionic acid and acetate: propionate ratio showed a quadratic effect, the lower values about 8 hours, the highest production to 7 hours, and the highest ratio of 9 hours after feeding, respectively. The acetic acid production and total SCFA were influenced by the diets, but the diets that contained cassava and alfalfa showed the highest values. The degradability of DM, CP and NDF were affected by the diets, the diets with cassava and cassava + alfalfa had the highest effective degradability. Thus, showing that the cassava and alfalfa can replace the corn and soybean meal concentrates, without changing the dry matter intake and the rumen environment of goats, improving the production of acetic acid and the degradability of the diet.